Sosialisasi Pembuatan Kerajinan Tangan Gelang Dan Cincin Dalam Peningkatan Keterampilan Anak Sanggar Bimbingan Gombak Utara Di Kuala Lumpur Negara Malaysia - Rina Andriani; Nurul Ain Harahap; Wina Surya Marda; Zaifatur Ridha (peduli riset dan pengabdian masyarakat, 2024)
The bracelet and ring handicraft making activity is one of the efforts in improving children's skills and creativity at the North Gombak Guidance Centre, Kuala Lumpur. The purpose of this activity is to provide a forum for knowledge about handicrafts to children and train them in producing unique works of art. The method of implementation of this activity is done through socialisation, material provision, and direct practice in making handicrafts to children in the guidance studio. This activity was carried out with a qualitative descriptive method and direct observation as a data collection technique. The results of the discussion show that learning arts and crafts provides great benefits for the development of children. The activity of making bracelets and rings from yarn and pearl trinkets is not only fun, but also easy to do. The children were guided directly by Ustazah Dahlia and KKN students from Jam'iyah Mahmudiyah Islamic College in Tanjung Pura in making the crafts. They were given explanations about the materials used, examples of craft forms, and how to make them. Through this activity, the children can improve their skills, self-confidence, independence, and productivity. Thus, children in the North Gombak Guidance Centre can benefit from these activities and are expected to be encouraged to continue developing themselves in the field of skills.